Association of water, sanitation, hygiene and food practices with enteric fever in a paediatric cohort in North India. Issue 1 (26th April 2022) - Dudeja, Nonita; Sinha, Bireshwar; Goyal, Nidhi; Arya, Alok; Revi, Anitha; Dutta, Ankita; More, Deepak; Chakravarty, Aparna; Kumar, Chandra Mohan; Rongsen-Chandola, Temsunaro
Abstract : Background: Our aim was to assess the association of water, sanitation and hygiene (WASH) and food practices with culture-confirmed enteric fever in children <15 years of age. Methods: We followed a cohort of 6000 children from an urban low socioeconomic neighbourhood in South Delhi for 2 years to estimate burden of culture-confirmed enteric fever. Risk ratios (RRs) were estimated to study the association between WASH practices and enteric fever. We assessed the microbiological quality of drinking water and conducted geospatial analysis to evaluate the distribution of enteric fever cases around households with contaminated drinking water. Results: A total of 5916 children in 3123 households completed survey. Piped water (82%) was the major source of household drinking water. One-third (32%) of the households treated water before consumption. Almost all households had sanitary toilets (99.9%) and 16% used shared toilets. Consumption of food from street vendors and unnamed ice creams more than once a week was observed in children from 12.7% and 38.4% households, respectively. Eighty culture-confirmed enteric fever cases were reported. The risk of enteric fever was 71% higher in children belonging to households having food from outside once a week or more (RR 1.71, 95% CI 1.00 to 2.94). The RR for enteric fever in children living in households with availability of safe drinking water was 0.75 (95% CI 0.45 to 1.26). We found that 14.8% of the households had presence of coliforms or Escherichia coli in their household drinking water. The odds of having a case of enteric fever within a 5 and 25 m buffer zone around households with contaminated drinking water were 4.07 (95% CI 0.81 to 20.5) and 1.44 (95% CI 0.69 to 3.00), respectively. Conclusion: In addition to WASH practices, optimal food hygiene may have a role in urban low socioeconomic population to control enteric fever. Trial registration number: CTRI / 2017/09/009719.